Evaluation of Microalgae as Immunostimulants and Recombinant Vaccines for Diseases Prevention and Control in Aquaculture - Ma, Ke; Bao, Qiuwen; Wu, Yue; Chen, Siwei; Zhao, Shuxin; Wu, Haizhen; Fan, Jianhua (Frontiers in Bioengineering and Biotechnology, 2020)
Microalgae are often used as nutritional supplements for aquatic animals and are widely used in the aquaculture industry, providing direct or indirect nutrients for many aquatic animals. Microalgae are abundant in nature, of high nutritional value, and some of them are non-toxic and rich in antioxidants so that they can be explored as a medicinal carrier for human or animals. Natural wild-type microalgae can be adopted as an immunostimulant to enhance non-specific immune response and improve growth performance, among which Haematococcus pluvialis, Arthrospira (Spirulina) platensis, and Chlorella spp. are commonly used. At present, there have been some successful cases of using microalgae to develop oral vaccines in the aquaculture industry. Researchers usually develop recombinant vaccines based on Chlamydomonas reinhardtii, Dunaliella salina and cyanobacteria. Among them, in the genetic modification of eukaryotic microalgae, many examples are expressing antigen genes in chloroplasts. They are all used for the prevention and control of single infectious diseases and most of them are resistant to shrimp virus infection. However, there is still no effective strategy targeting polymicrobial infections and few commercial vaccines are available. Although several species of microalgae are widely developed in the aquaculture industry, many of them have not yet established an effective and mature genetic manipulation system. This article systematically analyzes and discusses the above problems to provide ideas for the future development of highly effective microalgae recombinant oral vaccines.